Heat and mass transfer phenomenon and aligned entropy generation with simultaneous effect for magnetized ternary nanoparticles induced by ferro and nano-layer fluid flow of porous disk subject to motile microorganisms - Raza, Qadeer; Wang, Xiaodong; Ali, Bagh; Qureshi, M. Zubair Akbar; Chamkha, Ali J. (Numerical heat transfer. Part A, Applications, 2025)
This articles focus the dynamics of fluid conveying ternary solid particles, nano-layer, and magnetic field effects subject to porous disks. The magnetized ternary nanoparticles induced by Ferro and nano-layer are considered due to their unusual characteristics like extraordinary thermal conductivity, which are significant in advanced nanotechnology, heat exchangers, material sciences, and electronics. To avoid possible sedimentation of tiny particles, the motile microorganisms are also considered in the elaborated fluid problem. The main objective of this comprehensive study is the enhancement of heat transportation. In this study, we also investigate the physical dynamics of entropy generation, particularly emphasizing viscous dissipation related to joule heating effects. The mass transfer equation was employed to monitor the chemical interaction with diverse nanoparticles. The results of comparative and numerical validation agree well. The approach of stable and accurate numerical boundary value problem of fourth order code (bvp4c) is applied to solve the nonlinear system of ordinary differential equations. Many useful engineering results are summarized here, including the skin friction coefficient ( C f ) , Nusselt number (Nu), Sherwood number (Sh), and motile number (Nn). For both porous disks, several non-dimensional parameter effects are depicted graphically and tabulated. The results show that the increasing the number of nanolayer particles slows the rate of the temperature profile in both porous disks, associated with the expansion ratio, Reynolds number, and magnetic field number. Moreover, increasing the values of the density ratio number results in an increase in the flow of microorganisms profile in both porous disks. Increasing the values of the diffusivity parameters and the temperature difference enhances the flow of entropy generation.